Criticality assessment of global freshwater resource use: adapting abiotic resource criticality frameworks – water SCARCE - Marinova, S.; Bach, V.; Link, A.; Finkbeiner, M. (Elsevier, 2025)
Freshwater scarcity is a growing global concern, driven by increasing demand, environmental changes, and unsustainable management practices. Assessing water resources from a criticality perspective highlights the importance and reliance of various sectors on specific water sources. Existing abiotic resource criticality assessments provide valuable frameworks for evaluating the vulnerability and supply risks of resources but have predominantly focused on minerals, overlooking the freshwater criticality. Thus, we developed Water SCARCE, a novel and integrative approach for freshwater criticality assessment. This framework builds on existing abiotic resource criticality assessment methods, ESSENZ and SCARCE while aligning with the only existing water criticality evaluation approach developed by Sonderegger et al. (2015). The methodology of Water SCARCE adapts and expands existing criticality categories and indicators to deliver water criticality characterisation factors. Key modifications of the ESSENZ and SCARCE methods include integrating parameters specific to freshwater, resulting in a framework addressing water criticality dimensions like availability, demand, and environmental and social factors. When comparing the abiotic resource criticality methods, Water SCARCE, and Sonderegger et al. (2015), all address supply risk, vulnerability, and environmental aspects. However, Sonderegger uniquely incorporates governance and geopolitical components, such as political stability of neighbouring countries, which adds a perspective on supply risks influenced by transboundary water resources. Despite this strength, Sonderegger's method lacks a distinct social dimension and water quality considerations, areas where Water SCARCE approach provides additional insights, resulting in a more comprehensive evaluation of freshwater criticality. Our findings reveal that aspects such as physical and socio-economic availability, as well as social acceptability, are relevant for assessing water as a resource. The study highlights the innovative contributions of Water SCARCE in bridging methodological gaps and enhancing criticality evaluations. Future applications of the framework include the calculation of global characterisation factors, enabling product-level assessment of freshwater criticality.